The Influence of Independence and Task Complexity on Auditor Performance With Job Satisfaction as A Mediating Variable - Siti Zahra Junaedi; Sulhendri Sulhendri (Eduvest - Journal of Universal Studies, 2025)
This study examines the influence of auditor independence and task complexity on auditor performance, with job satisfaction acting as a mediating variable. Utilizing a quantitative approach, data were collected from auditors working in public accounting firms (KAP) in DKI Jakarta through surveys. The research findings indicate that while task complexity has a significant effect on auditor performance, independence does not significantly influence performance either directly or through job satisfaction. Job satisfaction was found to mediate the relationship between task complexity and auditor performance. These results suggest that managing task complexity and enhancing job satisfaction are essential to improving auditor pdasdaserformance. The study emphasizes the importance of creating a work environment that reduces the negative effects of task complexity while fostering job satisfaction to improve audit outcomes. This research contributes to the understanding of factors influencing auditor performance and provides practical recommendations for improving auditing practices within firms.